Literasi Digital melalui Pelatihan Pembuatan Video di TBM Teras Mburi - Pujiastuti, Ana (Media Informasi, 2024)
Mobile phones have benefits for elementary school-age children. However, if they are used excessively, there are risks, including affecting children's emotional development and making it difficult for children to socialize. Based on the above phenomenon, TBM Teras Mburi created video-making training for elementary school-age children in the surrounding area. The aim is for elementary school-age children to have additional knowledge that cell phones can be used not only for playing games and social media but also to produce work in a fun way. The approach used in this best practice is descriptive qualitative, which tells the best experience in solving the problems faced related to the phenomenon of the rise of elementary school-age children who are addicted to using cell phones. The stages consist of pre-production, production, and post-production. The result is that this training can provide knowledge, motivation, and encouragement for elementary school-age children around TBM Teras Mburi to be more productive and carry out positive activities. As for the impact of this activity, firstly, there was a change in the participants' behavioral patterns in using cell phones, from passive consumers to active producers. Second, it increases children's insight into the creative video-making process. Third, there is less concern about the excessive use of cell phones, which negatively affects social interactions because friends must coordinate, communicate, and work together to make videos.